The effect of using pelletized media on the production of alpha-amylase by solid state fermentation - Arquiza, Apollo C. (2000)
The study investigated the effect of using pelletized media on the performance of a solid waste fermentation (SSF) system, particularly on an aerated packed bed bioreactor. the SSF utilized Aspergillus oryzae grown on rice bran-cassava starch medium (10:1 mass ration) to produce a-amylase. The pelletized medium had an effective diameter of 5 mm. compared to less than 0.0833 mm. for the unpelletized one. The column bioreactor used had a diameter of 100 mm and a total bed volume of 1.3 dm^3. At an aeration rate of 1.20 vessel volume per minute (vvm) and 84 hours fermentation time, the pelletized medium gave a yield of 589 dextrinizing unit (DUN)/g dry medium compared to 179 (DUN)/g dry medium for the unpelletized medium at the same conditions. Compared to that reported for SSF in static trays, the pelletized medium gave 6.52. greater value. at 3.40 vvm aeration rate, the yield (pelletized medium) was 611 DUN/g dry medium, which was 1.55 times that for the unpelletized medium and 5.44 times that for trays.